Sulfidation and selenidation of nickel nanoparticles. Issue 4 (14th October 2020) - Lynch, Brian B.; Kelliher, Andrew P.; Anderson, Bryan D.; Japit, Alexander; Spencer, Michael A.; Rizvi, Mehedi H.; Sarac, Mehmet F.; Augustyn, Veronica; Tracy, Joseph B.
Abstract: Transition metal chalcogenide nanoparticles (NPs) are of interest for energy applications, including batteries, supercapacitors, and electrocatalysis. Many methods have been established for synthesizing Ni NPs, and conversion chemistry to form Ni oxide and phosphides from template Ni NPs is well‐understood. Sulfidation and selenidation of Ni NPs have been much less explored, however. We report a method for the conversion of Ni template NPs into sulfide and selenide product NPs using elemental sulfur, 1‐hexadecanthiol, thiourea, trioctylphosphine sulfide, elemental selenium, and selenourea. While maintaining mole ratios of 2 mmol sulfur/selenium precursor: mmol Ni, products with phases of Ni3 S2, Ni9 S8, NiS, NiSO4 ·6H2 O, Ni3 S4, Ni3 Se2, and NiSe have been obtained. The products have voids that form through the Kirkendall effect during interdiffusion. Trends relating the chemical properties of the precursors to the phases of the products have been identified. While some precursors contained phosphorus, there was no significant incorporation of phosphorus in any of the products. An increase of the NP size during sulfidation and selenidation is consistent with ripening. The application of Ni sulfide and selenide NPs as electrocatalysts for the hydrogen evolution reaction is also demonstrated. Abstract : Nickel sulfide and selenide nanoparticles (NPs) have energy applications, including electrocatalysis of the hydrogen evolution reaction. Sulfidation and selenidation reactions are performed on nickel template NPs, using a library or sulfur and selenium precursors. All reactions yield hollow NP products, consistent with the Kirkendall effect. Trends relating the chemical properties of the precursors to the phases of the products are identified.